Odnos in znanje kliničnih mentorjev zdravstvene nege o varnosti pacientov - Robida, Andrej (Obzornik zdravstvene nege, 2014)
Introduction: Nursing clinical mentors need current knowledge and skills to successfully train nursing students. The aim of this research was to evaluate the attitude and knowledge of patient safety among clinical mentors of the Faculty for Health Care Jesenice (FHCJ). Methods: Opportunity sampling was used among clinical nursing mentors who participated in the workshop on quality in health care in the organization of FHCJ. A translated World Health Organization questionnaire about attitudes and knowledge on patient safety was used. The response rate was 52 % (n = 36). Kruskal-Wallis and logistic regression tests were employed with SPPS, version 20. Results: In the domain of personal attitudes towards patient safety more than 90 % of answers were positive. Student attitudes of knowledge about patient safety, safety of the health care system and personal influence over safety did not reach the level of good patient safety practice. The overall percentage of correct answers about patient safety knowledge was 25.5 %. The number of years in nursing and the number of hours of previous formal education did not predict the level of correct answers about patient safety - (x2 (4, N = 31) = 8.83, p = 0.07). Discussion and conclusion: In this research nursing clinical mentors demonstrated an insufficient knowledge about patient safety.
Keywords: education; izobraževanje; mentorji; mentors; nursing; nursing care; patient safety; varnost pacientov; zdravstvena nega